Improved microstructure and increased mechanical properties of additive manufacture produced TI-6AL-4V by interpass cold rolling - Martina, Filomeno; Williams, Stewart W.; Colegrove, Paul A. (University of Texas, 2013)
Distortion, residual stress and mechanical property anisotropy are current challenges in additive manufacturing (AM) of Ti-6Al-4V. High-pressure, interpass rolling was applied to linear AM parts and resulted in a change from large columnar prior β grains to a completely equiaxed microstructure with grains as small as 89 μm. Moreover, α laths thickness was also reduced to 0:62 μm. The change in material microstructure resulted in a substantial improvement of all mechanical properties tested, which were also totally isotropic. In rolled specimens, maximum measured strength and elongation were 1078MPa and 14% respectively, both superior to the wrought material. Distortion was reduced to less than half. Rolling proved to be a relatively easy method to overcome some of the critical issues which keep AM from full industrial implementation.